Exploring the avian gut microbiota: current trends and future directions - Waite, David W.; Taylor, Mike (Frontiers in Microbiology, 2015)
Birds represent a diverse and evolutionarily successful lineage, occupying a wide range of niches throughout the world. Like all vertebrates, avians harbour diverse communities of microorganisms within their guts, which collectively fulfil crucial roles in providing the host with nutrition and protection from pathogens. Across the field of avian microbiology knowledge is extremely uneven, with several species accounting for an overwhelming majority of all microbiological investigations. These include agriculturally important birds, such as chickens and turkeys, as well as birds of evolutionary or conservation interest. In our previous study we attempted the first meta-analysis of the avian gut microbiota, using 16S rRNA gene sequences obtained from a range of publicly available data sets. We have now extended our analysis to explore the microbiology of several key species in detail, to consider the avian microbiota within the context of what is known about other vertebrates, and to identify key areas of interest in avian microbiology for future study.